Design of ultra-wide tetra band phased array inverted T-shaped patch antennas using DGS with beam-steering capabilities for 5G applications. Issue 5 (14th June 2020) - Anas, Muhammad; Shahid, Hifsa; Rauf, Abdul; Shahid, Abdullah
Abstract: A novel 1 × 4 phased array elliptical inverted T-shaped slotted sectored patch antenna with defected ground structure (DGS), resonate at proposed ultra-wide tetra band at 28, 43, 51, and 64 GHz with high gain and beam-steering capabilities is presented. An inverted T-shaped slotted stub is used with the sectored patch to achieve ultra-wideband properties. In order to resonate the antenna at four different bands, DGS of round bracket slot is etched on the ground. The 1 × 4 phased arrays are used at the top edge and bottom edge of mobile PCB with high gain. The simulation results show that the antenna has four ultra-wide bands: 25.8–29.7, 40.6–44.6, 49.2–53.1, and 62.2–74 GHz with a maximum gain of 16.5 dBi at 51 GHz. The phased array antenna is capable to steer its main beam within ±30° at the 26, 28, and 43 GHz, using appropriate phase shifts of each antenna element. The proposed millimeter wave antenna is particularly suitable for cellular infrastructures and can be a candidate for emerging 5G mobile applications. The availability of an additional 11.8 GHz (62.2–74 GHz) of contiguous unlicensed spectrum will allow the launching of new exciting wireless services.